An Analysis of Illocutionary Acts in Selected Poems by Carl Sandburg - Emelia Janesia Cendy Panambunan (Social Science Academic, 2026)
This research aims to classify the types of illocutionary acts found in five poems by Carl Sandburg. To analyze which type of illocutionary act is most dominant in these five poems, a qualitative research was used in this study. Data were collected from Sandburg’s poetry texts obtained from reliable sources, primarily the official edition of his poetry collection, which was used for documentation. The results of the research indicate that there are five types of illocutionary acts found in the five poems by Carl Sandburg, and the most dominant illocutionary act is the representative. Thus six poems contain the illocutionary types: representative, expressive, directive, declarative, and commissive, and the most dominant illocutionary type found in the six poems is the representative.